Recovery after African Olive invasion: can a 'bottom‐up' approach to ecological restoration work?. (17th December 2014) - Cuneo, Peter; Leishman, Michelle R.
Summary African Olive (Olea europaea ssp. cuspidata) is a densely crowned evergreen small tree, native to eastern Africa that is highly invasive in areas where it has been introduced, including Hawaii and Australia. Invasion by African Olive threatens Cumberland Plain Woodland, a critically endangered grassy eucalypt woodland from western Sydney, Australia, through the formation of a dense mid‐canopy excluding the regeneration of native species. We established a 3‐year field experiment to determine the effectiveness of direct seeding and fire, as techniques for early stage restoration of a 2 ha historically cleared and degraded Cumberland Plain Woodland site after the removal of African Olive. Direct seeding was able to re‐establish a native perennial grass cover which was resistant to subsequent weed invasion and could be managed as an important first stage in woodland restoration with fire and selective herbicide. Fire was able to stimulate some germination of colonising native species from the soil seed bank after 15 years of African Olive invasion; however, germination and establishment of native shrubs from the applied seed mix was poor. We propose a 'bottom‐up' model of ecological restoration in such highly degraded sites that uses a combination of direct seeding and stimulation of the soil seed bank by fire, which could be applicable to other degraded grassy woodland sites and plant communities.